The Anthropocene as colonial discourse. (February 2020) - Simpson, Michael
Research on the Anthropocene has emerged fast and furiously across academic disciplines in recent years. While some have suggested that this concept signifies a rupture with the philosophical foundations of Western modernity, this paper stresses the continuities between the Anthropocene and its antecedents. I trace the development of the concept from the late 18th century through to the mid-20th century, identifying several colonial and Eurocentric features of these earlier accounts of the Anthropocene. I then proceed to question whether contemporary debates about the Anthropocene and its periodization evoke similar problematic narratives about progress, modernity, and civilization. In the closing section of this article, I discuss whether or not the Anthropocene can be salvaged as an analytical category without reproducing these colonial logics. Here, I conclude that regardless of whether the term is discarded or redeemed, critical scholars can help to problematize and destabilize the concept's investment in the dominant onto-epistemological categories of Western modernity, thereby opening up possibilities for the plurality of ways of thinking and knowing to shape this conversation about the social and ecological predicaments of the colonial present.